2014
DOI: 10.1002/mc.22198
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of metallothionein gene polymorphisms on the risk of lung cancer in a Japanese population

Abstract: Metallothioneins (MTs) are cysteine-rich proteins that act as antioxidants. A case-control study was conducted to assess the effects of gene polymorphisms in the MT region on the risk of lung cancer in Japanese subjects: 769 lung cancer cases and 939 non-cancer controls. Associations were evaluated using logistic regression models with adjustment for potential confounders (age, sex, and lifestyle factors including smoking, drinking, and green-yellow vegetable intake). We found five polymorphisms in the MT-1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Three loci, rs11076161 A, rs964372 C, and rs719179 C were protective against OSSC, whereas rs805239 A alleles were associated with increased risk (Zavras et al, 2011). A modest increased risk of lung cancer was associated with a polymorphism (rs7196890) in the MT1 gene, but the effect size decreased as the amount of smoking increased (Nakane et al, 2015). Thus, MT polymorphisms, particularly those in the non-coding regions of the gene, may have a role in the functionality of MT in responses to environmental agents associated with respiratory tract injuries and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Three loci, rs11076161 A, rs964372 C, and rs719179 C were protective against OSSC, whereas rs805239 A alleles were associated with increased risk (Zavras et al, 2011). A modest increased risk of lung cancer was associated with a polymorphism (rs7196890) in the MT1 gene, but the effect size decreased as the amount of smoking increased (Nakane et al, 2015). Thus, MT polymorphisms, particularly those in the non-coding regions of the gene, may have a role in the functionality of MT in responses to environmental agents associated with respiratory tract injuries and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that genetic factors contribute to BC susceptibility [3-7]. Recent studies showed the expression of the Metallothionein 2A ( MT2A ) gene increased in some human neoplasms [8-10]. And, it has been reported that the high expression of MT2A associated with the stage and prognosis of tumors [9, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…In a Japanese population, five polymorphisms were reported to be moderately associated with the risk of lung cancer. [25] In a population from the United States, individuals with the GG and GA genotype of rs8052394 were shown to have lower hair mercury levels than those with the AA genotype. The MT1A (A>G) genotype distribution in Iran differed in comparison to those reported in Europe (P < 0.0001), [26] Spain (P < 0.0001), [24] Italy (P < 0.0001), [21,27] Bulgaria (P < 0.0001), [28] the United States (P < 0.0001), [16] China (P < 0.0001), [24] Nepal (P < 0.0001) [12] and Taiwan (P < 0.0001) [29,30] (Table 3).…”
Section: Mt1a Missense (A>g) Genotype and Allele Frequencymentioning
confidence: 99%